MODEL PENGAWASAN DEWAN KEHORMATAN PENYELENGGARAAN PEMILIHAN UMUM (DKPP) DALAM PENYELERANGGARAAN PEMILU BERBASIS PARTISIPATIF MASYARAKAT - Kholik, Saeful (Universitas Wiralodra, 2022)
This article aims to find the form or model of supervision of the honorary board for the implementation of general elections (DKPP) in the implementation of community-based elections. Given the reality that there are still many community activities that cannot be accommodated, this is caused by the absence of an explicit model or arrangement of the community reporting process. Therefore, this article identify the following problems: 1. What is the model of Supervision of the Honorary Council for the Implementation ofGeneral Elections (DKPP) in organizing elections based on community participation, 2. What is the position of the authority and authority of the DKPP in the positive legal perspective in Indonesia? The research method used is juridical-normative, which is a way of validating a problem through an approach to norms, principles, and rules that exist in society. Based on the findings, it explains that the community participates in maintaining, controlling, and even being part of the implementation of general elections or regional head elections, and explains the position of the DKPP which has a vital position and function to maintain justice for election organizers or participants who are suspected of having committed violations of the code of ethics.